2014
DOI: 10.1111/clr.12525
|View full text |Cite
|
Sign up to set email alerts
|

EPA‐coated titanium implants promote osteoconduction in white New Zealand rabbits

Abstract: Objectives: To investigate the effect of eicosapentaenoic acid (EPA)-coated Ti implants on osteoconduction in white New Zealand rabbit mandibles.Material and methods: Sandblasted and cleansed planar titanium specimens with a size of 5 9 5 9 1 mm were coated on one side with 0.25 vol% eicosapentaenoic acid (EPA). The other side of the specimens was kept highly polished (the control side). These specimens were inserted in rabbit mandibles. Twelve rabbits were randomly assigned into three study groups (n = 4). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…Moreover, this was in line with a study performed on white New Zealand rabbits using implants coated with eicosapentaenoic acid that was shown to enhance osteoconduction and anchorage of the implant to the surrounding bone [ 14 ]. Also, it was in line with a study performed by Park et al, 2007, where the results concluded that Ca and vitamin D supplementation promoted bone healing around dental implants [ 32 ].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Moreover, this was in line with a study performed on white New Zealand rabbits using implants coated with eicosapentaenoic acid that was shown to enhance osteoconduction and anchorage of the implant to the surrounding bone [ 14 ]. Also, it was in line with a study performed by Park et al, 2007, where the results concluded that Ca and vitamin D supplementation promoted bone healing around dental implants [ 32 ].…”
Section: Discussionsupporting
confidence: 83%
“…Fish oils are rich sources of the omega-3 polyunsaturated fatty acids (PUFA) eicosapentaenoic (EPA) acid and dexahexaenoic acid (DHA) that are distributed in almost all body cells, thus impacting cell functions, cell communication, production of various biomolecules and antioxidant activities [ 13 ]. Furthermore, decreased bone resorption or enhanced bone formation may be a consequence of the dual bone-sparing effect of omega-3 [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, these implants can only be termed "mechanical implants" because they lack essential biological properties, such as anti-microbial or osteogenic ability. Therefore, many researchers have performed a lot of studies to improve the biological properties of SS or titanium alloy, including increasing biological coating or adding biological elements, [1][2][3][4][5][6] and have achieved significant progress.…”
Section: Introductionmentioning
confidence: 99%